NLRP3 inflammasome in peripheral blood monocytes of acute coronary syndrome patients and its relationship with statins. Issue 5 (August 2015) - Altaf, Afrasyab; Qu, Peng; Zhao, Yang; Wang, Hongyan; Lou, Dayuan; Niu, Nan
Abstract : Objectives: Despite recent advances in the understanding of the role of NLRP3 inflammasomes in coronary atherosclerosis, further work on their activation and clinical implications remains to be performed. In this study, we aimed to evaluate the effect of the dose of rosuvastatin on NLRP3 and cathepsin-B expression in peripheral blood monocytes in patients with acute coronary syndrome. Methods: A total of 123 participants were enrolled in this study; these included acute myocardial infarction (AMI) patients ( n =53), unstable angina patients (UA, n =40), and normal controls ( n =30). AMI and UA patients were divided into high-dose rosuvastatin (20 mg) and low-dose rosuvastatin (5 mg) groups. NLRP3, cathepsin-B, and downstream cytokine expressions were appropriately evaluated using real-time PCR, flow cytometry, western blotting and enzyme-linked immunosorbent assay. The concentrations of serum inflammatory markers were also evaluated for correlation with NLRP3 levels. Results: AMI and UA patients had higher NLRP3, cathepsin-B, interleukin-18 (IL-18), pro-IL-18, IL-1β, and pro-IL-1β expressions as compared with the control group ( P <0.05). This corresponded with higher levels of serum total cholesterol, serum low-density lipoprotein cholesterol, and oxidized low-density lipoprotein in UA and AMI patients ( P <0.05). Rosuvastatin at a concentration of 20 mg led to a significant decrease ( P <0.05) in the expressions of NLRP3, cathepsin-B, and their downstream cytokines as compared with 5 mg rosuvastatin ( P >0.05) from baseline to 4 weeks. This study also showed a positive correlation between NLRP3, cathepsin-B, and downstream inflammatory mediators. Conclusion: NLRP3 is involved in inflammation that leads to atherosclerosis. A high dose of rosuvastatin can modulate the inflammatory process of atherosclerosis by downregulating the expression of NLRP3, cathepsin-B, and their downstream mediators. These findings provide insight into the pathogenesis and management of acute coronary syndrome, with NLRP3 as the potential target.